Pigmented dentigerous cyst in a patient with multiple dentigerous cysts of jaws: A case report - Shahrabi Sh; Lotfalian MT (Tehran University of Medical Sciences, 2006)
Abstract: In this paper, an unusual case of pigmented dentigerous cyst in a 37-year-old Iranian man with multiple dentigerous cysts of maxilla and mandible is reported. In addition to the characteristic histopathologic features of dentigerous cyst, numerous melanin granules which were distributed throughout the epithelial lining of one of these cysts were also noted. The histochemical study using Fontana's staining indicated that the pigment was melanin and many of the cells containing melanin were immunohistochemically positive for S-100 protein. Although no firm conclusion could be drawn from the present case regarding melanin origin in dentigerous cyst, the possible histogenesis of melanocytes in odontogenic lesions is discussed.